Efektivitas Pembelajaran Daring (online) terhadap Pembentukan Karakter Disiplin Siswa Kelas XI DKV. 1 SMKN 7 Bone - Rusdi, Muhammad; Ahmad, Ahmad; Nurmi, Nurmi; Ashari, A. Muh. Ikbal (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research is a qualitative research with a qualitative descriptive method. The data collection techniques used were observation, interview and documentation techniques with the research subjects being Civics teachers and four class XI DKV students. To find out the effectiveness of online learning for class XI DKV students in the even semester of 2022/2023, it can be said that online learning is less effective because from the data obtained from teacher and student interviews, the application system for online learning using online media, namely the WhatsApp and Google form applications still exists some students have difficulty accessing learning applications due to several obstacles that occur but also some students and teachers have been greatly assisted in the online learning process.